Evidence based treatment for lupus nephritis: present perspectives and challenges - Xagas, Efstathios; Drouzas, Konstantinos; Liapis, George; Lionaki, Sophia (Frontiers in Nephrology, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease known for its high heterogeneity among individuals, which affects various organs including the kidneys. Lupus nephritis (LN) is a frequent and life-threatening manifestation of the disease, with up to 50% of patients developing kidney involvement. Classification of renal involvement in lupus is based on specific histopathological findings, guiding therapeutical decisions. Immunosuppressive therapy, particularly glucocorticoids combined with cyclophosphamide or mycophenolate mofetil, has been the mainstay of treatment for many years, while rates of complete remission have not changed dramatically. Despite advancements in therapy, in an important proportion of patients LN leads to end-stage kidney disease (ESKD). Emerging therapies including belimumab, voclosporin, and obinutuzumab offer promising results in improving renal outcomes, especially in refractory or relapsing disease. Maintenance therapy is crucial to prevent disease flares and preserve renal function. Supportive measures including lifestyle modifications and non-immunosuppressive pharmacological interventions are nowadays also essential in managing LN. This review emphasizes recent advances of therapy and challenges regarding treatment optimization with strategies to improve long-term outcomes.